An insight into anti-adipogenic properties of an Oroxylum indicum (L.) Kurz extract - Tanaporn Hengpratom; Gordon M. Lowe; Griangsak Eumkeb (BMC, 2020)
Abstract Background Oroxylum indicum fruit extract (OIE) has been reported to inhibit the development of adipocytes. However, the exact mechanism of its metabolic activity is not clearly defined. This study attempted to investigate whether OIE was involved in disrupting the cell cycle, glucose metabolism, and mitochondrial function in 3 T3-L1 cells. Methods The effect of the OIE on cell cycle progression was measured by flow cytometry along with observing the expression of the cycle regulator by immunoblotting. The effect of the OIE on glucose metabolism was investigated. The amount of glucose uptake (2-NBDG) influenced by insulin was determined as well as the protein tyrosine phosphorylation (PY20), and glucose transporter4 (GLUT4) expression was determined by immunoblotting assay. Mitochondria are also essential to metabolic processes. This study investigated mitochondrial activity using fluorescent lipophilic carbocyanine dye (JC-1) and mitochondria mass by MitoTracker Green (MTG) staining fluorescence dyes. Finally, cellular ATP concentration was measured using an ATP chemiluminescence assay. Results Treatment with OIE plus adipogenic stimulators for 24 h arrested cell cycle progression in the G2/M phase. Moreover, 200 μg/mL of OIE significantly diminished the expression of the insulin receptor (IR) and GLUT4 protein compared to the untreated-adipocytes (P < 0.05). The mitochondrial membrane potential (MMP) was significantly reduced (24 h) and increased (day 12) by OIE compared to untreated-adipocytes (P < 0.05). However, OIE maintained MMP and ATP at a similar level compared to the pre-adipocytes (day 12). Transmission electron microscope (TEM) results demonstrated that OIE could protect mitochondria deformation compared to the untreated-adipocytes. Conclusion These results suggest that the inhibitory effect of the OIE on adipogenesis may potentially inhibit the cell cycle and phosphorylation of IR, leading to a decrease in glucose uptake to the cells. The OIE also slows down the mitochondrial activity of the early phase of cell differentiation, which can also inhibit the development of fat cells.